LOCAL WISDOM-BASED CREATIVE ECONOMY DEVELOPMENT STRATEGY TO ACHIEVE COMPETITIVE ADVANTAGE IN THE ERA OF THE INDUSTRIAL REVOLUTION 4.0 IN GUNUNGKIDUL REGENCY - Rohmah, Siti; Mulatsih, Nurdiana Tri (Jurnal REP (Riset Ekonomi Pembangunan), 2022)
The Creative Economy prioritizes one's ability to create a product in the form of goods or services, both arts and crafts followed by creative ideas, culture, and technology which will later become a new concept to contribute to national economic growth. Gunungkidul Regency has excellent creative economic potential, namely culinary, fashion, craft, performance art, and film. Bobung hamlet, Putat village, Patuk district has a center for making batik wooden masks where the creations are made with superior local wisdom patterns. The study was conducted using the Mix Methods by examining objects by collecting quantitative and qualitative data and using a SWOT analysis tool (Strength, Weakness, Opportunity, Threat). This analysis involves internal and external elements of strengths, weaknesses, opportunities, and threats. The results of the research show that by employing both internal and external analysis, it is found in the quadrant I position, called aggressive strategy. An aggressive strategy emphasizing production on quality and innovation of local consumer products by empowering or employing local products produced by their own region and developing triple helix by involving government, intellectuals, and business as a collaboration partner, which is the strongest strategy in the batik wood mask craft.